Comparison of the accuracy of NovApex apex locator and radiographic method: in vivo/ex vivo study - Shahriar Shahi; Saeed Rahimi; Amin Salem Milani; Mohammad Asghari Jafarabadi; Gholam Reza Djoorabbaf Naghsh (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2011)
INTRODUCTION: Determination of the canal working length with radiographs has many drawbacks. Electronic apex locators have been developed to overcome some of these problems. Recently, a newly designed apex locator called NovApex has been introduced. All the studies conducted to determine the accuracy of NovApex have been carried out in-vitro on extracted teeth. The aim of this in vivo study was to evaluate the accuracy of NovApex compared with traditional radiographic method. MATERIALS & METHODS: Twenty-five patients whose lower molars that were candidates for extraction were selected. The teeth were accessed, and the radiographic working length was determined by measuring the length of the initial file 0.5mm short of the radiographic apex. Then, NovApex apex locator was used to measure the electronic working length. Subsequently, the tooth was extracted, and the actual working length was measured by introducing a size #15 K-file into each canal until the file tip was visible at the apex, then 1.5mm was subtracted to attain the working length. Cohen's Kappa was computed for each of the methods versus actual working length as a measure of reliability. The accuracies were compared using Chi-square test. RESULTS: The accuracy of NovApex apex locator and radiographic method in detecting the apical end point within ±0.5mm was 74.7% and 68%, respectively; this was not significantly different (P<0.001). CONCLUSION: The NovApex apex locator is useful in detecting the apical end point with the accuracy similar to radiographic method. However, neither technique is fully reliable in detecting the apical end point of the canal.